Optimalisasi pajak daerah dan pembiayaan daerah untuk belanja modal: Studi empiris pada Pemerintah Daerah Di Jawa Barat - Tutik Aisah; Desy Nur Pratiwi; Wikan Budi Utami (Kurva: Jurnal Ekonomi Manajemen Keuangan dan Bisnis, 2025)
This study aims to analyze the influence of local taxes, regional revenues, balancing funds, and regional financing on capital expenditure in regency and city governments in West Java Province during the period 2020–2023. Capital expenditure is a crucial indicator that supports regional infrastructure development and is influenced by various sources of local government funding. This research employs a quantitative approach using multiple linear regression analysis. The population consists of all regencies and city governments in West Java Province, totaling 27 local governments (18 regencies and nine cities). The sampling technique used is purposive sampling based on the availability of complete regional budget realization data for the 2020–2023 period. Based on these criteria, a total sample of 108 observations was obtained. The results show that local taxes and regional financing have a significant effect on capital expenditure, while regional retributions and balancing funds have no significant effect. These findings indicate that increases in capital expenditure are more strongly influenced by the optimization of local tax revenues and the financing strategies adopted by local governments.